Precarious Creativity : Global Media, Local Labor - Sanson, Kevin; Curtin, Michael (Book collections on Project MUSE., 2016)
"Precarious Creativity examines the seismic changes confronting media workers in an age of globalization and corporate conglomeration. This pathbreaking anthology peeks behind the hype and supposed glamor of screen media industries to reveal the intensifying pressures and challenges confronting actors, editors, electricians, and others. The authors take on pressing conceptual and methodological issues while also providing insightful case studies of workplace dynamics regarding creativity, collaboration, exploitation, and cultural difference. Furthermore, it examines working conditions and organizing efforts on all six continents, offering broad-ranging and comprehensive analysis of contemporary screen media labor in such places as Lagos, Prague, Hollywood, and Hyderabad. The collection also examines labor conditions across a range of job categories that includes, for example, visual effects, production services, and adult entertainment. With contributions from such leading scholars as John Caldwell, Vicki Mayer, Herman Gray, and Tejaswini Ganti, Precarious Creativity offers timely critiques of media globalization while also intervening in broader debates about labor, creativity, and precarity"--Provided by publisher